Het Groninger Museum in Heerlen. - Groninger Museum, Groningen; Raadhuis, Heerlen (Heerlen : Gemeentebestuur, 1976)
Alkema, Wobbe ; Altink, Jan ; Appel, Karel ; Baljau, Joost ; Benner, Gerrit ; Constant ; Cortier, Amedee ; Dekkers, Ad ; Diederen, Jef ; Dijstra, Johan ; Elias, Etienne ; Hansen, Job G. ; van der Heyden, J.C.J. ; Jansen, Han ; De Keyser, Raoul ; Kuipers, Abe ; Lucassen, Reinier ; Nanninga, Jaap ; Raveel, Roger ; Sanders, Har ; Struycken, Peter ; Wagemaker, Jaap ; Werkman, H.N. ; Westerik, Co ; Wiegers, Jan ; van der Zee, Jan
Het Groninger Museum in Heerlen, Raadhuis, Heerlen, 1976
boek